A developmentally stable chromatin structure in the human beta-globin gene cluster. - Forrester, W C (1986)
The DNase I-hypersensitive sites in the human embryonic beta-globin gene region have been mapped in erythroid-enriched fractions of disaggregated fetal livers, in adult nucleated red blood cells, and in fetal brain tissue. Our analysis of a region extending 11 kilobases (kb) 5' of the epsilon-globin gene reveals many minor nuclease-hypersensitive sites and one major site located 6.1 kb upstream of the epsilon-globin gene. All of these hypersensitive sites are erythroid-specific, and the major site is stable throughout erythroid development. As assayed by nuclear runoff transcription, little or no epsilon-globin gene expression is detectable in fetal or adult erythroid cells. Thus, the presence of the major hypersensitive site 5' of the epsilon-globin gene in both fetal and adult erythroid cells demonstrates that this site is not specifically correlated with transcription of the gene or with a particular stage of development. Rather, this site may reflect an early event in erythroid differentiation. In addition, DNase I has been used to probe the overall sensitivity of epsilon-globin chromatin in fetal erythroid cells. Our findings indicate that the epsilon-globin gene as well as the other genes in the beta-globin cluster reside within the chromatin domain that is more DNase I-sensitive than "bulk" chromatin.